2018
DOI: 10.1109/jsac.2018.2825159
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Transmit Antenna Selection for Massive MIMO Wiretap Channels

Abstract: In this paper, we study the impacts of transmit antenna selection on the secrecy performance of massive MIMO systems. We consider a wiretap setting in which a fixed number of transmit antennas are selected and then confidential messages are transmitted over them to a multi-antenna legitimate receiver while being overheard by a multi-antenna eavesdropper. For this setup, we derive an accurate approximation of the instantaneous secrecy rate. Using this approximation, it is shown that in some wiretap settings und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…Similarly to the Appendix A, we can derive the expressions of I 3 and I 4 as: then, substituting (19), we can derive the following expression of I 3 as:…”
Section: Appendix Cmentioning
confidence: 99%
“…Similarly to the Appendix A, we can derive the expressions of I 3 and I 4 as: then, substituting (19), we can derive the following expression of I 3 as:…”
Section: Appendix Cmentioning
confidence: 99%
“…The performance limits of massive MIMO systems under practical antenna selection algorithms using large scale system analysis that maximizes the energy efficiency are studied in [18]. In [19], the impacts of transmit antenna selection on the secrecy performance of massive MIMO systems are analyzed. It is found that in some wire tap settings under antenna selection, the increase in the number of active antennas improves the secrecy performance of the system up to some optimal number.…”
Section: Introductionmentioning
confidence: 99%
“…In [17] and [18], antenna selection algorithms are proposed with the purpose of attaining only utmost energy efficiency rather than considering sum rate maximization, interference, and complexity analysis. The effect of transmit antenna selection on the secrecy performance of massive MIMO systems is discussed in [19]. In [20], the complexity of antenna selection increases with the number of antennas which is very high for a massive MIMO system.…”
Section: Introductionmentioning
confidence: 99%
“…In the past years, many researches on antenna-selectionaided MIMOME channels were presented [6]- [10]. For example, Yang et al,in [6] and [7] derived closed-form expressions for the secrecy outage probability (SOP) in MIMOME channels under transmit antenna selection (TAS) with or without the impact of antenna correlation, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Later, the achievable secrecy performance of MIMO wiretap channels in the presence of imperfect CSI was analyzed in [9]. In contrast to the explicit analysis in [6]- [9], Asaad et al,in [10] proposed asymptotically approximated results for both the average secrecy rate and the SOP in the limit of largescale MIMOME systems under the norm-based TAS protocol. However, all these aforementioned works focused on the Gaussian input assumption.…”
Section: Introductionmentioning
confidence: 99%